Information and Communications Security 17th International Conference, ICICS 2015, Beijing, China, December 9-11, 2015, Revised Selected Papers - Qing, Sihan; Okamoto, Eiji; Kim, Kwangjo; Liu, Dongmei (Security and Cryptology, 2016)
This book constitutes the thoroughly refereed post-conference proceedings of the 17th International Conference on Information and Communications Security, ICISC 2015, held in Beijing, China, in December 2015. The 24 revised full papers and 19 short papers presented were carefully selected from 148 submissions. The papers provide the latest results in research and development in the field of information security and applied cryptology.